A Partial Identification Approach to Identifying the Determinants of Human Capital Accumulation: An Application to Teachers - Nirav Mehta (Center for Economic Studies and ifo Institute (CESifo), 2022)
This paper views teacher quality through the human capital perspective. Teacher quality exhibits substantial growth over teachers' careers, but why it improves is not well understood. I use a human capital production function nesting On-the-Job-Training (OJT) and Learning-by-Doing (LBD) and experimental variation from Glewwe et al. (2010), a teacher incentive pay experiment in Kenya, to discern the presence and relative importance of these forces. The identified set for the OJT and LBD components has a closed-form solution, which depends on experimentally estimated average treatment effects. The results provide evidence of an LBD component, as well as an informative upper bound on the OJT component.
Keywords: I20; I28; J20; J24; J45; C10; 330; human capital; teacher quality; on-the-job training; learning-by-doing; partial identification